Factors Influencing the Students’ Choice of Accounting as a Major - Syed Ali, Sharifah Sabrina; Tinggi, Micheal (Universiti Malaysia Sarawak (UNIMAS), 2013)
Accounting program, a specialized professional program—including financial accounting, accounting information system, cost and managerial accounting, taxation, auditing, financial statement analysis, accounting theory and practices including professional standards such as International Financial Reporting Standards (IFRS) or Generally Accepted Accounting Principles (GAAP), financial management and public sector accounting—prepares the students to practice the profession of accounting and perform any related business function. The Universiti Malaysia Sarawak (UNIMAS) introduced Accounting program in September 2012. This study examines the impact of factors like past achievements, personal interests, job prospect, media, family members and peers on the choice of students in accepting the offer of ‘Accounting’ as a major in UNIMAS.